Os tradutores e o erotismo em “Miss Algrave” de Clarice Lispector - Correia, Rebecca de Lima (2023)
Clarice Lispector’s enigmatic writing has stood the test of time, spanning decades and being translated into several languages. Faced with the overwhelming force of the writer's letter in An Apprenticeship or The Book of Pleasures, this research aims to unravel the eroticism present in The Via Crucis of the Body, published in 1974. The main objective is to analyse, through collation, whether the translations of the short story “Miss Algrave” by translators Alexis Levitin, with Soulstorm - The Stations of the Body (1989), and Katrina Dodson, with The Complete Stories - The Via Crucis of the Body (2018), are in line with the erotic effect produced by Clarice’s writing. In order to understand the translations, it is important to profile the translators. To do this, we will consider: who the translator is, the vision and concept of translation, the purpose of translation, and finally, we will highlight the translator’s experience in the field of translation. In addition, we need to test a hypothesis: does the translator’s gender influence the “translator’s horizon” or the transposition of the erotic trait contained in “Miss Algrave”? Lispector uses language primarily as a means of movement to reveal her erotic writing. As a theoretical contribution, this research will draw on the Russian literary critic Viktor Chklóvski (2019), in “The Art of Procedure”, through the concept of ostranênie or “strangeness”. And in order to appreciate the translators’ versions, I will follow the method of critical analysis developed by Antoine Berman (2009) in Toward a Translation Criticism: John Donne, which consists of applying specific criteria to better evaluate translations. With regard to the eroticism in Clarice’s writing, we will dialogue with Eliane Robert Moraes, Lynn Hunt, Alexandrian and Paz, among others.